A randomised controlled crossover trial comparing a polymeric with a semi-elemental oral nutritional supplement on fluid and sodium status in patients with a jejunostomy - Alison Culkin; Beth Rye; Jeremy MD Nightingale (Intestinal Failure)
Background: Patients with a short bowel need to restrict oral fluid to reduce stoma/fistula output. Some patients require oral nutritional supplements (ONS) to meet nutritional requirements. There is limited research on ONS for patients with a short bowel. This study aimed to compare polymeric verses semi-elemental ONS on jejunal wet weight and sodium output. Materials and methods: Patients were included if they had < 200 cm of small bowel to a jejunostomy or an enterocutaneous fistula. Patients fasted from midnight then were randomly allocated to consume 200 ml of either Vital 1.5® or Ensure Plus® over 30 min. Jejunal output and urine were collected for 6 h during which patients remained nil by mouth. Jejunal and urine outputs were weighed, and samples sent for analysis. After a day washout, patients were swapped to the other ONS. Differences between the two study periods were assessed using multilevel regression. Results: Ten patients completed, 4 females: 6 males, mean age 59.2 years, mean small bowel length 95 cm. Jejunal wet weight (P < 0.001) and jejunal sodium (P = 0.003) were significantly higher on Vital 1.5® compared to Ensure Plus® with a mean difference of 0.1 kg and13mmol respectively. There was no difference in faecal sodium balance (P = 0.16), urine sodium (P = 0.38) or urine volume (P = 0.56). Conclusion: A semi-elemental ONS results in a greater jejunal wet weight loss compared to a polymeric one. The amount is small but the daily cumulative loss will be greater.